The new Isaac : tradition and intertextuality in the Gospel of Matthew - Huizenga, Leroy Andrew, 1974- (Novum Testamentum, Supplements, 2009)
Gospel scholarship has long recognized that Matthean Christology is a rich, multifaceted tapestry weaving multifold Old Testment figures together in the person of Jesus. It is somewhat strange, therefore, that scholarship has found little role for the figure of Isaac in the Gospel of Matthew. Employing Umberto Eco's theory of the Model Reader as a theoretical basis to ground the phenomenon of Matthean intertextuality, this work contends that when read rightly as a coherent narrative in its first-century setting, with proper attention to both biblical texts and extrabiblical traditions about Isaac, the Gospel of Matthew evinces a significant Isaac typology in service of presenting Jesus as new temple and decisive sacrifice.